Evaluation of Apoptosis and Autophagy Inducing Potential of Berberis aristata, Azadirachta indica, and Their Synergistic Combinations in Parental and Resistant Human Osteosarcoma Cells - Sengupta, Pracheta; Raman, Sukanya; Chowdhury, Rajdeep; Lohitesh, K.; Saini, Heena; Mukherjee, Sudeshna; Paul, Atish (Frontiers in Oncology, 2017)
Cancer is a multi-factorial disease and hence can be effectively overcome by a multi-constituently therapeutic strategy. Medicinal plant extracts represent a perfect example of such stratagem. However, minimal studies have been done till date that portray the effect of extraction techniques on the phyto-constituent profile of plant extracts and its impact on anti-cancer activity. In the present study, we have evaluated the anti-cancer potential of methanolic extracts of Berberis aristata root and Azadirachta indica seeds prepared by various extraction techniques in human osteosarcoma (HOS) cells. Soxhlation extract of B. aristata (BAM-SX) and sonication extract of A. indica (AIM-SO) were most effective in inducing apoptosis in parental drug sensitive, as well as resistant cell type developed by repeated drug exposure. Generation of ROS and cell cycle arrest preceded caspase-mediated apoptosis in HOS cells. Interestingly, inhibition of autophagy enhanced cell death suggesting the cyto-protective role of autophagy. Combination studies of different methanolic extracts of BAM and AIM were performed, amongst which, the combination of BAM-SO and AIM-SO (BAAISO) was found to show synergism (IC50 10.27μg/ml) followed by combination of BAM-MC and AIM-MC (BAAIMC) with respect to other combinations in the ratio of 1:1. BAAISO also showed synergism when it was added to cisplatin resistant HOS cells (HCR). Chromatographic profiling of BAM-SX and AIM-SO by high performance thin layer chromatography (HPTLC) resulted in identification of berberine (Rf 0.55), palmitate (Rf 0.50) in BAM-SX and azadirachtin A (Rf 0.36), azadirachtin B (Rf 0.56), nimbin (Rf 0.80) and nimbolide (Rf 0.43) in AIM-SO. The cytotoxic sensitivity obtained can be attributed to the above compounds. Our results highlight the importance of extraction technique and subsequent mechanism of action of multi-constituential B. aristata and A. indica against both sensitive and drug refractory HOS cells.